(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Synthesis of novel quinazoline derivatives was performed from reaction of N-benzoyl substituted piperazine-1-carbothioamide with 4-(2-chlormethyl) quinazoline-4-yloxy phenyl benzamide derivatives and screened for their in vitro cytotoxic activity by MTT assay. The cell lines used were MCF 7 (Breast cancer cell), HCT 15 (Colon cancer cell line), and VERO (Normal epidermal kidney cell). Result of screening on cell line showed moderate to good cytotoxic activity for all the compounds. Compound GNU 02 (IC50 = 7.94 µM, MCF), GNU 12 (IC50 = 8.43 µM, HCT) and GNU 25 (IC50 = 9.41 µM, HCT) was found to be most active compared to standard gefitinib (IC50 = 1.51 µM HCT, IC50 =22.37 µM MCF). Structure activity relationship of synthesized analogs suggested that the attachment of electron withdrawing groups like Nitro, Chloro gave better cytotoxic activity then unsubstituted phenyl and electron donating groups. Activity by substituted piperazine at 2nd position of thiazole linked with quinazoline scaffold gave better activity in the order of H > CH3 > C6H5. Our findings may impart new direction to medicinal chemists and biochemists for further investigations of quinazoline-thiazole containing cytotoxic agents.